2017
DOI: 10.1039/c7ra04162d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-catalyst-free growth of graphene on insulating substrates by ammonia-assisted microwave plasma-enhanced chemical vapor deposition

Abstract: We study the metal-catalyst-free growth of uniform and continuous graphene films on different insulating substrates by microwave plasma-enhanced chemical vapor deposition (PECVD) with a gas mixture of C 2 H 2 , NH 3 , and H 2 at a relatively low temperature of 700-750 C. Compared to growth using only C 2 H 2 and H 2 , the use of NH 3 during synthesis is found to be beneficial, in transforming vertical graphene nano-walls into a layer-by-layer film, reducing the density of defects, and improving the graphene qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 63 publications
(60 reference statements)
3
36
0
Order By: Relevance
“…This severely limits the use of transferred graphene layers in semiconductor device technology. Hence, direct fabrication of graphene on non-metal substrates like silicon (Si) 13 , germanium (Ge) 14 17 , silicon dioxide (SiO 2 ) 18 , 19 and sapphire (Al 2 O 3 ) 18 , 19 has become an alternative route in the last few years.…”
mentioning
confidence: 99%
“…This severely limits the use of transferred graphene layers in semiconductor device technology. Hence, direct fabrication of graphene on non-metal substrates like silicon (Si) 13 , germanium (Ge) 14 17 , silicon dioxide (SiO 2 ) 18 , 19 and sapphire (Al 2 O 3 ) 18 , 19 has become an alternative route in the last few years.…”
mentioning
confidence: 99%
“…In addition, according to simulations and experimental results, Zhang et al showed that silicon substrate in the RF system is surrounded by an electric sheath field that changes the local Figure 12. A schematic of (a) MW-PECVD setup and (b) the zoom-in of the growth of graphene (reprinted with permission from [96]).…”
Section: Radio Frequencymentioning
confidence: 99%
“…Graphene can also be grown using PECVD, where the growth temperatures can be lowered substantially by lowering the energy barrier for hydrocarbon pyrolysis and dissociation. It can also be utilized for growing graphene on insulating substrates [130][131][132][133], skipping entirely the transfer process. Recently, PECVD has been used in conjunction with copper foam by Wei et al to grow graphene on flexible glass [134].…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%